Inhibition of T-lymphocyte mitogenic responses and effects on cell functions by bovine herpesvirus 1. - Carter, J J (1989)
The mitogenic response of bovine peripheral blood mononuclear cells stimulated by concanavalin A (ConA) was suppressed by infectious bovine herpesvirus 1 (BHV-1). Proliferation in response to interleukin-2 (IL-2) by IL-2-dependent lymphocyte cultures was also inhibited by BHV-1. Although inhibition of mitogenesis approached 100%, less than 1 cell in 1,000 was productively infected by BHV-1 in ConA-stimulated cultures. Neither conditioned medium from mitogen-stimulated peripheral blood mononuclear cell cultures nor human recombinant IL-2 reversed suppression by the virus. Infection by BHV-1 did not influence the expression of IL-2 or IL-2 receptor mRNA in ConA-stimulated cultures, nor did it affect the cytolytic capabilities of lymphocytes. The data suggest that the inhibition of T-lymphocyte proliferation is the result of a nonproductive BHV-1 infection.